Modelling of Thermoelectric Power Generation by Porous Media Burner - Henriquez-Vargas, L; Bubnovich, V (Italian Association of Chemical Engineering - AIDIC, 2011)
A system for converting combustion heat into electric power is proposed in this work on the basis of super-adiabatic combustion in a thermoelectric porous element. A lean gas mixture is introduced into the porous medium, where the gas flow rate changes at a regular interval of time. As a result, the combustion front remains at a predetermined region of the porous medium. A steady state temperature distribution is established along the flow direction, resulting in a steep temperature gradient in the thermoelectric porous element. Numerical simulation showed that the total thermal efficiency reaches 4.6 %, almost equal to the conversion efficiency of the thermoelectric element itself. Consequently, using the proposed system, the chemical energy can be effectively converted into electric power. Copyright © 2011, AIDIC Servizi S.r.l.